2014
DOI: 10.1007/s00277-014-2212-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of intraocular involvement in primary CNS lymphoma: experience from the G-PCNSL-SG1 trial

Abstract: The impact of intraocular involvement (IOL) in primary CNS lymphoma (PCNSL) has not been sufficiently evaluated. Here, we present the analysis of IOL in the only completed randomized phase III trial in PCNSL. The G-PCNSL-SG1 study evaluated the role of whole-brain radiotherapy in primary therapy of PCNSL. Data of the 526 eligible study patients were checked, and clinical characteristics, therapy, and outcome of patients with IOL diagnosed at study inclusion were analyzed. Ophthalmologic examination at study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 21 publications
(18 reference statements)
0
16
0
Order By: Relevance
“…Grimm et al (14) reported that patients with PCNSL with and without intraocular involvement had similar PFS and OS rates; however, their study only included patients with ocular and parenchymal involvement at diagnosis. Kreher et al (15) demonstrated that patients with IOL had significantly inferior PFS and OS rates compared with non-IOL patients. In this study, not all patients received an ophthalmological evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Grimm et al (14) reported that patients with PCNSL with and without intraocular involvement had similar PFS and OS rates; however, their study only included patients with ocular and parenchymal involvement at diagnosis. Kreher et al (15) demonstrated that patients with IOL had significantly inferior PFS and OS rates compared with non-IOL patients. In this study, not all patients received an ophthalmological evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the search for other parameters supporting a prognostic discrimination has been widely futile except for some tissue markers including the expression of bcl-6 which has been associated with a favourable course of the disease (6). Furthermore, it has been reported that intraocular involvement in PCNSL may represent a negative prognostic indicator (7). In contrast, the relevance and application of minimally invasive biomarkers such as blood-borne patterns (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, single site involvement of either eye or CNS has a better prognosis than the double site involvement (PVRL and PCNSL) (71,96). The 5-year survival rate is higher in patients with isolated PVRL than in those with CNS involvement (71,82).…”
Section: Pvrl Prognosismentioning
confidence: 99%
“…However, the duration of complete remission did not differ between patients with and without CNS involvement (71). Kreher reported that the median progression-free survival in the PCNSL patients with intraocular involvement (3.5 months) was shorter than the ones without PVRL (8.3 months) (96). That is, intraocular involvement at diagnosis of PCNSL was an independent negative prognostic indicator for the progression-free survival and overall survival (96).…”
Section: Pvrl Prognosismentioning
confidence: 99%
See 1 more Smart Citation